Synthesis of Thieno[3, 4‐b]thiophene‐Based Donor Molecules with Phenyl Ester Pendants for Organic Solar Cells: Control of Photovoltaic Properties via Single Substituent Replacement. Issue 4 (4th April 2016) - Wada, Yuya; Asada, Yuki; Ikai, Tomoyuki; Maeda, Katsuhiro; Kuwabara, Takayuki; Takahashi, Kohshin; Kanoh, Shigeyoshi
Abstract: We have synthesized novel thieno[3, 4‐ b ]thiophene‐based π‐conjugated molecules with phenyl ester pendants as electron donor materials for solution‐processed organic photovoltaics (OPVs). As the electron‐withdrawing power of the p ‐substituent on the phenyl ester pendant in these molecules was enhanced, their highest occupied molecular orbital (HOMO) energy levels deepened by up to 0.3 eV. Accordingly, when OPV devices were fabricated from these materials, the open‐circuit voltage ( V oc ) was increased by up to 40 mV. A linear correlation was found to exist between the Hammett constants of the p ‐substituents and the HOMO levels of the molecules as well as the V oc of the corresponding OPV devices. The direct comparison with the corresponding benzyl ester‐type molecule demonstrated that an electronic influence of the single p ‐substituent on the pendant can be transmitted to the π‐conjugated backbones through a phenyl ester linkage to control the photovoltaic performances. Abstract : Thieno[3, 4‐ b ]thiophene‐based donor molecules with phenyl ester pendants have been synthesized as electron donor materials for organic photovoltaics (OPVs). The influence of the p ‐substituents on the phenyl esters on their frontier orbital energy levels and photovoltaic performances were carefully investigated. We found that there was a linear correlation between the Hammett constants of the p ‐substituents and the HOMO levels of the π‐conjugated molecules as well as the open‐circuit voltages of the corresponding OPV devices.